Bioactive compounds of endophytic fungi isolated from seaweeds inhibiting some pathogen bacteria - สาแม อามีนา; หิรัญรัตน์ อัษฎาวุธ; โอทอง สมพงศ์; ศุภพล พฤทฐิภร; อินทระสังขา นุกูล (KKU Science Journal, 2017)
This research was conducted by isolating the endophytic fungi from 8 seaweeds collecting from coastal areas of 4 southern provinces, Thailand. There were 82 fungal isolates obtained. By using morphological and molecular approaches for identification, we found that the endophytic fungi belonged to 3 genera, 4 species and other 25 unidentified, namely, Penicillium spp. Aspergillus fumigates, Aspergillus niger, Aspergillus flavus, Aspergillus rhizopodus, and Rhizopus spp. The primary screening with Agar plug diffusion technique, we found only 1 species, namely A. rhizopodus has showed the highest inhibition activities against some pathogens bacteria. Therefore, only A. rhizopodus isolate was then selected for further study solvent extraction with sequential solvent extract with ethyl acetate and methanol. The crude extracts were tested for the inhibitory effect against selected pathogenic bacteria. Only ethyl acetate extract has showed the inhibition activity against 9 pathogens bacteria and antibiotic resistant bacteria which were Bacillus cereus, Staphylococcus aureus ATCC 25923, Aeromonas hydrophila, Escherichia coli ATCC 25922, Klebsiella pneumoniae ATCC 700603, Pseudomonas aeruginosa ATCC 27853, Salmonella Stratford (ESBL), Salmonella Typhimurium (ESBL) and Salmonella Weltevreden (ESBL). This chemical has shown the highest inhibition activities against E. coli ATCC 25922 (Clear zone = 38.65±0.03 mm), S. aureus ATCC 25923 (Clear zone = 37.25±0.00 mm), and S. Weltevreden (ESBL) (Clear zone = 36.29±3.31 mm). These results were statistically significant difference at the confidence level of 99% (P< .01). These bioactive compounds produced by endophytic fungi could inhibit certain pathogens may be due to some components of these secondary metabolites which need to be studied in more details for their roles and structures.